Capital structure and bank profitability in Vietnam: A quantile regression approach - Tu DQ Le; Dat Thanh Nguyen (Journal of Risk and Financial Management, 2020)
We empirically investigate the impact of capital structure on bank profitability using a quantile regression method in the Vietnamese banking system during 2007-2019. Our results suggest that the nonlinear relationship between capitalization and bank profitability is only significant at the 90th quantile. This is the first study to conclude that the turning point of capital ratio increases throughout the profitability distribution. Our findings thus suggest that a continuous increase in bank capital requirements does not necessarily result in higher bank profitability.
Keywords: 330; bank profitability; capital structure; nonlinearity; quantile regression; Vietnam